2014
DOI: 10.5858/arpa.2013-0572-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Free Hemoglobin and Bilirubin on Heparin Monitoring by Activated Partial Thromboplastin Time and Anti-Xa Assay

Abstract: Context.-Elevated free hemoglobin (Hb) and bilirubinemia complicate extracorporeal membrane oxygenation and could affect unfractionated heparin (UH) therapy monitoring by anti-Xa assay and activated partial thromboplastin time (aPTT).Objectives.-To compare in vitro response of anti-Xa and aPTT assays to UH in samples with artificial hyperbilirubinemia and hyperhemoglobinemia and to estimate if this interference is also observed in vivo in pediatric extracorporeal membrane oxygenation.Design.-Measurement of aPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 18 publications
(19 reference statements)
2
44
0
Order By: Relevance
“…Patients with renal disease may have impaired clearance of enoxaparin and thus different dosing regimens of this medication. Patients with hyperbilirubinemia were excluded since the colormetric anti‐Xa assay can be affected by elevated serum bilirubin . Patients who received a significant portion of their anticoagulation treatment in the inpatient setting were excluded to avoid differences in anti‐Xa monitoring practices in the inpatient and outpatient settings.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with renal disease may have impaired clearance of enoxaparin and thus different dosing regimens of this medication. Patients with hyperbilirubinemia were excluded since the colormetric anti‐Xa assay can be affected by elevated serum bilirubin . Patients who received a significant portion of their anticoagulation treatment in the inpatient setting were excluded to avoid differences in anti‐Xa monitoring practices in the inpatient and outpatient settings.…”
Section: Methodsmentioning
confidence: 99%
“…A prior study by Kostousov et al reported that hemoglobin and bilirubin added to plasma samples resulted in a concentration dependent underestimation of heparin activity using an anti‐Xa heparin activity assay . At ~0.46 U/mL heparin and 200 mg/dL plasma hemoglobin the assay underestimated the heparin level by ~0.12 U/mL.…”
Section: Discussionmentioning
confidence: 96%
“…Since these assays are based on spectroscopic measurements of assay absorbance, typically at 405 nm, substances in the plasma sample that absorb at this wavelength may interfere in the assay. The most common interferences are due to hemolysis (plasma hemoglobin) or icterus (plasma bilirubin) . While the mechanism of the false low interference is not known, it has been hypothesized that hemoglobin binding to heparin might result in partial heparin neutralization .…”
Section: Introductionmentioning
confidence: 99%
“…Each test has its inherent advantages and disadvantages including availability, cost, turnaround time, influence from factors other than the effect of heparin, and laboratory interference, as well as varying amounts of data for the use of these tests in this setting (Table ). Although ACT is commonly used because of its availability, rapid turnaround time, and familiarity in the context of cardiopulmonary bypass, it appears to be the least reliable marker of heparin's effect during ECLS . Thromboelastography, which provides information about multiple aspects of the clotting cascade, may become more routinely applied in the future, especially if data emerge indicating that it can help optimize pump function and bleeding risk.…”
Section: Specific Ecls Management Considerationsmentioning
confidence: 99%
“…Although ACT is commonly used because of its availability, rapid turnaround time, and familiarity in the context of cardiopulmonary bypass, it appears to be the least reliable marker of heparin's effect during ECLS. [58][59][60][61] Thromboelastography, which provides information about multiple aspects of the clotting cascade, may become more routinely applied in the future, especially if data emerge indicating that it can help optimize pump function and bleeding risk.…”
Section: Prophylaxis and Management Of Infectious Complicationsmentioning
confidence: 99%